Recent Developments in Small-Molecule Fluorescent Probes for Cellular Senescence - Junyoung Park; Youngjun Lee; Jongmin Park (Chemosensors, 2024)
Cellular senescence is a recently emerged research topic in modern biology. Often described as a double-edged sword, it encompasses numerous essential biological processes, including beneficial effects such as wound healing and embryonic development, as well as detrimental contributions to chronic inflammation and tumor development. Consequently, there is an increasing need to unravel the intricate networks of senescence and develop reliable detection methods to distinguish it from related phenomena. To address these challenges, a variety of detection methods have been developed. In particular, small-molecule fluorescent probes offer distinct advantages such as suitability for real-time live cell monitoring and in vivo imaging, superior tunable properties, and versatile applications. In this review, we explored recent advancements in the development of small-molecule fluorescent probes toward monitoring cellular senescence by targeting various senescence-related biological phenomena. These phenomena include the upregulation of senescence-associated enzymes, perturbation of the subcellular environment, and increased endogenous ROS levels. Moreover, multi-senescence biomarker-targeting approaches are also discussed to improve their sensitivities and specificities for the detection of cellular senescence. With recent advances in senescence probe development, current challenges in this field are also discussed to facilitate further progress.